Effect of Phytobiotic Feed Additives Garlic (Allium sativum), Ashwagandha (Withania somnifera) and Shatavari (Asparagus racemosus) as Alternatives to Antibiotic on Feed Intake, Metabolizability of Nutrients and Balance Study in Broiler Chicks - Jediya, Hemant Kumar; Joshi, Monika; Sharma, S. K. (International Journal of Bio-resource and Stress Management, 2025)
An experiment was conducted during March to April, 2021 at Poultry unit of College of Veterinary and Animal Science, Navania, Vallabhnagar, Udaipur (Rajasthan), India planned to investigate the effect of phytobiotic feed additives viz., garlic, ashwagandha and shatavari as alternatives to antibiotic on feed intake, metabolizability of nutrients and balance study of broiler chicks. A total of 300 day-old broiler chicks (Cobb-400) were involved in the 42-days. The T1 i.e. control group was fed on basal diet, while T2 was supplemented with Oxy tetra cycline (OTC) powder @ 0.1 g kg-1 feed. T3 and T4 were supplemented with Garlic powder @ 0.75% and @ 1.50%. T5 and T6 were supplemented with Ashwagandha powder @ 0.75% and @ 1.50%. T7 and T8 were supplemented with Shatavari powder @ 0.75% and @ 1.50%. T9 was supplemented with Garlic powder @ 0.25%, Ashwagandha powder @ 0.25% and Shatavari powder @ 0.25%. T10 was supplemented with Garlic powder @ 0.50%, Ashwagandha powder @ 0.50% and Shatavari powder @ 0.50%. Feed intake was a highly significant (p<0.01) effect in different treatments groups. Non significant (p>0.05) effects were observed on dry matter and Organic matter metabolizability in different treatment groups. The metabolizability of crude protein, crude fibre and total ash was highly significant (p<0.01) effect and ether extract had a significant (p<0.05) effect due to treatments groups. The balance study of nitrogen, calcium and phosphorus had a highly significant (p<0.01) effect in different treatment groups.